Changes in the corticospinal tract after wearing prosthesis in bilateral transtibial amputation. (October 2017) - Lee, Sang Yoon; Kang, Si Hyun; Kim, Don-Kyu; Seo, Kyung Mook; Ro, Hee Joon; Kim, Jae Kyun
Background: After amputation, the brain is known to be reorganized especially in the primary motor cortex. We report a case to show changes in the corticospinal tract in a patient with serial bilateral transtibial amputations using diffusion tensor imaging. Case Description and Methods: A 78-year-old man had a transtibial amputation on his left side in 2008 and he underwent a right transtibial amputation in 2011. An initial brain magnetic resonance imaging with a diffusion tensor imaging was performed before starting rehabilitation on his right transtibial prosthesis, and a follow-up magnetic resonance imaging with diffusion tensor imaging was performed 2 years after this. Findings and Outcomes: In the initial diffusion tensor imaging, the number of fiber lines in his right corticospinal tract was larger than that in his left corticospinal tract. At follow-up diffusion tensor imaging, there was no definite difference in the number of fiber lines between both corticospinal tracts. Conclusion: We found that side-to-side corticospinal tract differences were equalized after using bilateral prostheses. Clinical relevance: This case report suggests that diffusion tensor imaging tractography could be a useful method to understand corticomotor reorganization after using prosthesis in transtibial amputation.